Mineral paragenesis and fluid inclusions of the Bincanai epithermal silver-base metal vein at Baturappe area, South Sulawesi, Indonesia - Irzal Nur; Arifudin Idrus; Subagyo Pramumijoyo; Agung Harijoko; Akira Imai (Geological Engineering Department Universitas Gadjah Mada, 2015)
The Baturappe prospect located at southern part of Sulawesi island, Indonesia, is a hydrothermal mineralization district which is characterized by occurrence of epithermal silver-base metal deposits. The mineralization is hosted in basaltic-andesitic volcanic rocks of the late Middle-Miocene Baturappe Volcanics. More than 20 units of quartz – base metal veins are distributed in the area, and one of the most significant is the Bincanai vein. This study is aimed to characterize the mineral paragenesis and to elucidate the physicochemical conditions of the formation of the deposit on the basis of mineral assemblage and fluid inclusion mictrothermometry. Sulphide assemblages in the vein indicate an intermediate sulfidation state epithermal; beside galena and sphalerite as the early stage minerals, chalcopyrite, tennantite, and tetrahedrite are also identified as the later stage. Microthermometric study of fluid inclusions in quartz indicates formation temperature of the vein ranges from about 230 to 280°C Histogram of homogenization temperature suggests that there are two generations of hydrothermal fluid responsible for the ore mineralization in the vein; the higher temperature range represents formation temperature of the base metal (galena, sphalerite), while the lower temperature range is correlate with the precipitation of the rest relatively lower temperature sulphides (chalcopyrite, pyrite, tetrahedrite, tennantite, polybasite, and Bi-Ag-Cu-Fe-bearing sulfide). The sequence is also consistent with the mineral paragenetic. The mean of salinity (2.0–2.5 wt.% NaCl eq.) indicates that fluid responsible for the mineralization in the Bincanai vein is relatively low-salinity fluid.